Penerapan Composite Performance Index (CPI) Sebagai Metode Pada Sistem Pendukung Keputusan Seleksi Penerima Beasiswa - Satria, Budy; Sidauruk, Acihmah; Wardhana, Raditya; Al Akbar, Abdussalam; Ihsan, M. Arinal (AI Society & STMIK Indonesia, 2022)
The selection process for scholarship recipients in higher education requires a measurable system. The problem that has been happening is that the procedures carried out by the scholarship provider still use a manual file examination system. Composite performance index is the method used in this study. The purpose of this study is to create a decision support system for the selection of scholarship recipients to be more systematic and time efficient in the process. There are 10 alternatives and 4 criteria, namely parental income, GPA, electricity usage ,and semesters. The results of this study were obtained 5 highest values are A7 t with a value of 235.00 rank 1, A4 with a value of 200.00 rank 2, A1 with a value of 134.14 rank 3 sequences, A5 with a value of 120.00 ranks 4, and A8 with a value of 91.67 sequences 5.